Modulating ATP binding cassette transporters in papillary renal cell carcinoma type 2 enhances its response to targeted molecular therapy. Issue 10 (23rd August 2018) - Saleeb, Rola M.; Farag, Mina; Lichner, Zsuzsanna; Brimo, Fadi; Bartlett, Jenni; Bjarnason, Georg; Finelli, Antonio; Rontondo, Fabio; Downes, Michelle R.; Yousef, George M.
Abstract : Papillary renal cell carcinoma (PRCC) is the most common nonclear cell RCCs and is known to comprise two histological subtypes. PRCC2 is more aggressive and is molecularly distinct from the other subtypes. Despite this, PRCCs are treated together as one entity, and they show poor response to the current therapies that do not target pathways implicated in their pathogenesis. We have previously detected ABCC2 (an ABC transporter), VEGF, and mTOR pathways to be enriched in PRCC2. In this study, we assess the therapeutic potential of targeting these pathways in PRCC2. Twenty RCC cell lines from the Cancer Cell Encyclopedia were compared to the Cancer Genome Atlas PRCC cohort (290), to identify representative PRCC2 cell lines. Cell lines were further validated in xenograft models. Selected cell lines were treated in vitro and in vivo (mice models) under five different conditions, untreated, anti‐VEGF (sunitinib), ABCC2 blocker (MK571), mTOR inhibitor (everolimus) and sunitinib + MK571. Sunitinib +ABCC2 blocker group showed a significant response to therapy compared to the other treatment groups both in vitro ( P ≤ 0.0001) and in vivo ( P = 0.0132). ABCC2 blockage resulted in higher sunitinib uptake, both in vitro ( P = 0.0016) and in vivo ( P = 0.0031). Everolimus group demonstrated the second best response in vivo . The double‐treatment group showed the highest apoptotic rate and lowest proliferation rate. There is an urgent need for individualized therapies of RCC subtypes that take into account their specific biology. Our results demonstrate that combined targeted therapy with sunitinib and ABCC2 blocker in PRCC2 has therapeutic potential. The results are likewise potentially significant for other ABCC2 high tumors. However, the results are preliminary and clinical trials are needed to confirm these effects in PRCC2 patients. Abstract : Papillary renal cell carcinoma type 2 is a particular form of aggressive kidney cancer. There is currently no known treatment for the disease. In this study, we attempted to block certain molecules in the tumor cells that are known to actively transport cancer medications, as we have previously found them to be very high that cancer. The addition of the blocker to conventional therapies produced significant reduction in live cancer cells and significantly less cancer growth in mice. The results are clinically meaningful and should be studied in patient clinical trials.